Is pain associated with subsequent job loss? A panel study for Germany - Alan Piper; David G. Blanchflower; Alex Bryson (Kyklos, 2022)
The cross-sectional association between pain and unemployment is well-established. But the absence of panel data containing information on pain and labor market status has meant that less is known about the direction of any causal linkage. Those longitudinal studies that do examine the link between pain and subsequent labor market transitions suggest results are sensitive to the measurement of pain and model specification. We contribute to this literature using large-scale panel data from the German Socio-Economic Panel (GSOEP) for the period 2002 to 2018. We show that workers suffering pain are more likely than others to leave their job for unemployment or economic inactivity. This probability rises with the frequency of the pain suffered in the previous month. The effect persists having accounted for fixed unobserved differences across workers, is apparent among those who otherwise report good general health and is robust to the inclusion of controls for mental health, life satisfaction and the employee's occupation.
Keywords: 300